2022
DOI: 10.1002/etc.5412
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Apoptosis in Bisphenol AF–Induced Neurotoxicity in Zebrafish Embryos

Abstract: Bisphenol AF (BPAF) is a structural counterpart of bisphenol A that is utilized in the food and beverage industry.The present study investigated the potential mechanisms in BPAF-induced neurotoxicity in zebrafish embryos. The BPAF concentrations (0.03, 0.1, 0.3, and 1.0 µM) had no obvious effect on hatching, mortality, and body length of zebrafish larvae, while curved tail and pericardial edema were observed in the 1.0 μM group at 72 and 96 h postfertilization (hpf). Locomotor activity of the larvae (at 120 hp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Several studies have shown that oxidative stress can reduce zebra sh survival and lead to malformation (Chowdhury and Saikia, 2022;Gyimah et al, 2022;Hahn et al, 2015). In combination with the zebra sh survival rate and growth and development, we selected 7 mmol L − 1 of H 2 O 2 to induce zebra sh.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that oxidative stress can reduce zebra sh survival and lead to malformation (Chowdhury and Saikia, 2022;Gyimah et al, 2022;Hahn et al, 2015). In combination with the zebra sh survival rate and growth and development, we selected 7 mmol L − 1 of H 2 O 2 to induce zebra sh.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, exposure to BPA and bisphenol analogs has been reported to affect neurotransmission; for example, AChE activity was clearly decreased in the hippocampus of mice with BPA (Luo et al, 2013) and in Daphnia magna with BPF (Liu et al, 2020). Besides, BPAF was also reported to inhibit dopaminergic signaling and metabolism of neurotransmitters in zebrafish (Gu et al, 2022; Gyimah et al, 2022). Consistent with the former result, CUR could significantly rescue the decreased AChE activity caused by BPAF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that under normal physiological conditions, sh and other vertebrates can rapidly clear ROS through antioxidant enzymes, such as superoxide dismutase and catalase [24]. However, some high-dose clinical drugs can cause excessive generation of reactive oxygen species (ROS) in tissues, thereby destroying major cellular macromolecules and inducing oxidative stress leading to cell damage and apoptosis [25][26].…”
Section: Discussionmentioning
confidence: 99%